DAMPAK KENAIKAN HARGA BAHAN BAKAR MINYAK (BBM) TERHADAP SEMBILAN BAHAN POKOK (SEMBAKO) DI KECAMATAN CILIMUS - Agnesya Tamara Grasella (Jurnal Ekonomi dan Bisnis (EK dan BI), 2022)
The recent increase in the price of fuel oil has had an impact on society. In addition to people's anger, the prices of nine basic commodities (sembako) were also affected, causing an increase. The price of fuel oil (BBM) is a determinant of prices for other commodities. So, if the price of fuel oil (BBM) rises, the price increase will be followed by price increases in other sectors as well. This study aims to determine the impact of rising prices for fuel oil (BBM) on nine basic commodities (sembako) in Cilimus District. The data used in this study is to distribute questionnaires to traders and employees who are willing to fill in the Cilimus traditional market. The research method used is descriptive quantitative. The results of the study show that the impact of rising prices for fuel oil (BBM) on nine basic commodities (Sembako) is seen from several indicators and respondents' responses including: a negative impact with a percentage of 100% it can be concluded that the increase in fuel prices (BBM) has a negative impact on nine basic commodities (sembako) in Cilimus sub-district.